Weighing the impact of obesity on female reproductive function and fertility. (21st October 2013) - Jungheim, Emily S; Travieso, Jennifer L; Hopeman, Margaret M
Abstract : Obesity in women is associated with serious reproductive sequelae. Given its prevalence among women of reproductive age, much recent attention has focused on the mechanisms by which obesity affects female reproductive function and fertility. This review summarizes the literature investigating the epidemiology and pathophysiology of obesity in women of reproductive age and proposes research strategies that may help inform approaches to improve reproductive function and outcomes among obese women.